MELATIH SOSIAL EMOSIONAL ANAK USIA 4-5 TAHUN MELALUI METODE LITERASI - Hariri Dwi Ratnaningrum Statistin Gerhani (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2022)
Social emotional ability is needed to be developed in early childhood era due to social emotional is early ability for children to interact with their environment. The importance of social emotional for early childhood is really needed for family and also teachers. In addition, the purpose of making this article is to practice children social emotional in early school before entering the formal school. It is needed because they only know family environment before formal school and social emotional needed before that. One of problem solving to practice the social emotional in this age is by literacy method. The writer expected through the literacy method, early childhood social emotional in dealing with others can be solved. Literacy is intensed by education practitioner due to create not only smart academically individu but also having critical thinking and logic.